Tomatidine Attenuates C48/80-induced Inflammatory Responses in HMC-1 Cells and is Associated with Modulation of the JNK/AP-1/NF-κB/Caspase-1 Pathway - Xiao, Xiyan; Yang, Shiyin (Current Topics in Medicinal Chemistry, 2025)
BackgroundExisting research has suggested that the JNK/AP-1/NF-κB/Caspase-1 pathway may account for the activation of HMC-1 mast cells under inflammatory circumstances, and our current study aims to validate whether Tomatidine could act as the candidate to modulate this pathway in Allergic Rhinitis (AR).ObjectiveThis study aimed to characterize the effect of Tomatidine on inflammation in C48/80-activated HMC-1 cells in vitro and to explore the underlying mechanisms involved.MethodsThe inflammation in HMC-1 cells was triggered via C48/80 induction to mimic the AR, and the effects of Tomatidine on the viability of HMC-1 cells were tested using the Cell Counting Kit-8 assay. Thereafter, the concentrations of inflammation-related cytokines, Interleukin-1β, tumor necrosis factor-α, as well as the histamine and β-hexosaminidase, were quantified by enzyme-linked immunosorbent assay. The activation status of the JNK/AP-1/NF-κB/Caspase-1 pathway in HMC-1 cells following C48/80 and/or Tomatidine intervention was determined based on immunoblotting assay.ResultsThe viability was elevated in HMC-1 cells following C48/80-induced activation, and the concentration of inflammation-related cytokines and mediators was increased as well. Meanwhile, the protein levels of active Caspase-1 and the phosphorylation of JNK/AP-1/NF-κB/Caspase-1 pathway-related proteins were also observed in HMC-1 cells after the treatment of C48/80. On the contrary, Tomatidine intervention suppressed the viability and the concentration of inflammation-related cytokines and mediators of modeled HMC-1 cells and led to the inactivation of the JNK/AP-1/NF-κB/Caspase-1 pathway in modeled HMC-1 cells.ConclusionOur study demonstrates that Tomatidine can attenuate C48/80-induced inflammatory responses in HMC-1 cells in vitro, potentially through modulation of the JNK/AP-1/NF-κB/Caspase-1 signaling pathway. These findings provide preliminary evidence supporting Tomatidine as a candidate for further investigation in allergic inflammation.
Keywords: Inflammation